Atmospheric convection, dynamics and topography shape the scaling pattern of hourly rainfall extremes with temperature globally - Yiannis Moustakis (Nature Portfolio, 2020)
In regions with deep convection, persistent large-scale dynamics and complex orography, hourly rainfall extremes diverge from expectations from the atmosphere’s water holding capacity, suggests a global analysis of station data, reanalyses and convection-permitting models.